An Analysis of the Role of Tobacco-Specific Nitrosamines in the Carcinogenicity of Tobacco Smoke - Buddy G. Brown; August J. Borschke; David J. Doolittle (SAGE Publishing, 2003)
Cigarette smoke is a complex mixture consisting of more than 4500 chemicals, including several tobacco-specific nitrosamines (TSNA). TSNA typically form in tobacco during the post-harvest period, with some fraction being transferred into mainstream smoke when a cigarette is burned during use. The most studied of the TSNA is 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). NNK has been shown to be carcinogenic in laboratory animals. Studies examining the carcinogenicity of NNK frequently are conducted by injecting rodents with a single dose of 2.5 to 10 μmol of pure NNK; the amount of NNK contained in all of the mainstream smoke from about 3700 to 14,800 typical U.S. cigarettes. Extrapolated to a 70-kg smoker, the carcinogenic dose of pure NNK administered to rodents would be equivalent to the amount of NNK in all of the mainstream smoke of 22 to 87 million typical U.S. cigarettes. Furthermore, extrapolating results from rodent studies based on a single injection of pure NNK to establish a causative role for NNK in the carcinogenicity of chronic tobacco smoke exposure in humans is not consistent with basic pharmacological and toxicological principles. For example, such an approach fails to consider the effect of other smoke constituents upon the toxicity of NNK. In vitro studies demonstrate that nicotine, cotinine, and aqueous cigarette "tar" extract (ACTE) all inhibit the mutagenic activity of NNK. In vivo studies reveal that the formation of pulmonary DNA adducts in mice injected with NNK is inhibited by the administration of cotinine and mainstream cigarette smoke. Cigarette smoke has been shown to modulate the metabolism of NNK, providing a mechanism for the inhibitory effects of cigarette smoke and cigarette smoke constituents on NNK-induced tumorigenesis. NNK-related pulmonary DNA adducts have not been detected in rodents exposed to cigarette smoke, nor has the toxicity of tobacco smoke or tobacco smoke condensate containing marked reductions in TSNA concentrations been shown to be reduced in any biological assay. In summary, there is no experimental evidence to suggest that reduction of TSNA will reduce the mutagenic, cytotoxic, or carcinogenic potential of tobacco smoke.